Rancang Bangun Aplikasi Kamus Tobelo - Indonesia Berbasis Android dengan Metode Booyer Moore - Wijaya, Adhitya Kurnia; Utomo, Mardi Siswo (LPPM UNIKA Santo Thomas, 2023)
North Halmahera Regency, located in North Maluku, is home to the Tobelo language, which serves as the original language of the region and is widely spoken throughout North Maluku. Unfortunately, many residents, particularly teenagers residing in the city and its surrounding areas, are not familiar with the Tobelo language. This lack of awareness can be attributed to the absence of Tobelo language instruction in schools. To address this issue and facilitate the introduction of the Tobelo language, a research project was undertaken. The objective was to develop an Android-based Tobelo language dictionary application, leveraging the Boyer-Moore method. The purpose of this application is to support the learning process and preservation of the Tobelo language. The Tobelo language dictionary application was created using the Java programming language and the Android Studio platform. Its design emphasizes an intuitive and user-friendly interface, enabling users to easily search for words and translate them from Tobelo to Indonesian. The implementation of the Boyer-Moore string search method ensures swift and efficient word search functionality within the application's extensive dictionary database.